The peculiarities of complex formation and energy transfer processes in lanthanide complexes with 2-(tosylamino)-benzylidene-N-benzoylhydrazone. Issue 13 (6th March 2018) - Kovalenko, Anton D.; Bushmarinov, Ivan S.; Burlov, Anatolii S.; Lepnev, Leonid S.; Ilina, Elena G.; Utochnikova, Valentina V.
Abstract : The understanding of the peculiarities of the energy transfer processes in europium complexes allowed to obtain the luminescence thermometer materials with the highest sensitivity value at above the liquid-nitrogen temperatures. Abstract : Depending on the local excess of lanthanide ions (Ln = Lu, Yb, Er, Dy, Tb, Gd, Eu, Nd) or 2-(tosylamino)-benzylidene- N -benzoylhydrazone (H2 L), lanthanide complexes, containing either a mono-deprotonated ligand (Ln(HL)2 X, X = Cl, NO3 ) or both mono- and dideprotonated ligands (Ln(L)(HL)), were preparatively obtained. The crystal structures of Lu(HL)2 Cl, Yb(L)(HL)(H2 O)2, Yb(L)(HL)(EtOH)2 (H2 O) and Er(L)(HL), determined by single crystal diffraction data or from powder diffraction data using Rietveld refinement, have shown the surprising resemblance. The study of luminescence temperature dependence of Eu(HL)2 Cl and Eu(L)(HL) showed that europium luminescence is quenched by thermally-activated 5 D0 → T1 energy transfer. Luminescent thermometers based on these complexes demonstrated the sensitivity of up to 7.7% at 85 K which is the highest value above liquid-nitrogen temperatures obtained to date.